EFFECT OF GAMMA IRRADIATION ON THE QUALITY AND MATING COMPETITIVENES OF FRUIT FLIES BACTROCERA DORSALIS IN THE CAGE SCALE - Nasution, Indah Arastuti; Elvinasari, Elvinasari; Hastuti, Dewi (Universitas Lampung, 2018)
Bactrocera dorsalis is an important fruit fly attack fruits and vegetables in Indonesia. Sterile Insect Technique (SIT) is sterilize with gamma irradiation, released as many as 9 x wild population, ecpected to mate but didn?t produce offspring. The research porpuse was to determine the effect of gamma irradiation on the quality and on the mating competitiveness in cage scale. The experimental design was completely randomized design with one factor was gamma irradiation dosee at 6 levels were 0 (control), 30, 50, 70, 90 and 110 Gy as many as 4 replicates. The result that the level of the radiation dose had a significant on the competitiveness and quality included the percentage of pupae became adult adult, sex ratio, the percentage of fly ability, the number of eggs produced (fecundity) and percentage hatching eggs. The quality decreased when increasing in radiation dose. The dose level didn?t affect the fecundity but affected the mating competitiveness in cage scale. The value total of mating campetitivenes was highest at a dose of 70 Gy treatment were 0.76 (5:1:1) and 0.79 (10:1:1), followed by dose of 50 Gy were 0,41 (5:1:1) and 0,50 (10:1:1).